Pengaruh Marketing mix terhadap keputusan pembelian Toyota Avanza tipe G di Surabaya - Wilson Setiawan (Jurnal Strategi Pemasaran, 2014)
This research aims to analyze the impact of elemen’s marketing mix such as product, price, place and promotion to Purchase Decision Toyota Avanza Type G at Surabaya. And then, between four element of marketing mix, the dominant element’s of marketing to affect Purchase Decision Toyota Avanza type G at Surabaya. This research was conducting by distributing questionnaires to 100 consumers of Toyota Avanza type G. Analysis tool used to measure the impact of Marketing Mix to Purchase Decisionis multiple linear regression.The result of this research show that product, price, place, and promotion handling have effect on Purchase Decision Toyota Avanza Type G at Surabaya. Factors that have the greatest influence (dominant) of Purchase Decision is product.